GAMBARAN SELF EFFICACY SISWA DI MTS NURUL HIDAYAH - Nadishabani Hatta; Ecep Supriatna; Muhamad Rezza Septian (IKIP Siliwangi, 2021)
The purpose of this study was to obtain empirical data regarding the level of student self-efficacy at MTs Nurul Hidayah. This study uses a descriptive method with a quantitative approach. Collecting data using a self-efficacy instrument that contains 38 statement items with a sample of 100 students in grades VII and VIII. The results showed that the level of self-efficacy of students in MTs Nurul Hidayah are in the medium category, which is between the high and low categories, most of which are quite capable and confident in their abilities. As for the aspect of the dimension of self-efficacy, the highest order of results is obtained at the 68% level dimension, followed by the generalization dimension 67%, and the last order is the strength dimension 64%. The results of this study are to determine the description of student self-efficacy at MTs Nurul Hidayah which should to be an aide for BK instructors as a work to assist with further developing understudy self-efficacy. Keywords: : Self efficacy. students